Critical care admission trends and outcomes in individuals with bronchiectasis in the UK. Issue 8 (17th November 2015) - Navaratnam, Vidya; Muirhead, Colin R.; Hubbard, Richard B.; De Soyza, Anthony
Abstract : Background: There are limited data on admission trends and outcomes of individuals with bronchiectasis admitted to intensive care (ICU). Using national critical care data, we analysed admissions to ICU and estimated outcomes in terms of mortality in individuals with bronchiectasis and chronic obstructive pulmonary disease (COPD) admitted to ICU. Methods: Using data from the Intensive Care National Audit and Research Centre, admissions from bronchiectasis and COPD from 1 January 2009 to 31 December 2013 were extracted. Crude admission rates for bronchiectasis and COPD were calculated and Poisson regression was used to estimate unadjusted annual admission rate ratios. We investigated changes to length of stay on ICU, ICU mortality and in-hospital mortality during the study period. We also compared mortality rates in people with bronchiectasis and COPD aged 70 or above. Results: We found an annual increase of 8% (95% Confidence Interval [CI] 2–15) in the number of ICU admissions from bronchiectasis, whilst the yearly increase in ICU admissions from COPD was 1% (95% CI 0.3–2). ICU and in-hospital mortality was higher in individuals with bronchiectasis compared with those with COPD, especially in people aged 70 years or above. Conclusion: Admission to ICU in people with bronchiectasis are uncommon, but are increasing in frequency over time, and carries a substantial mortality rate. This needs to be considered allocating health care resources and planning respiratory services.